Importance of anatomopathological analysis and histopathological examination for the diagnosis of suspected cases of syphilitic aneurysm - Tenório, Pedro Pereira; Tenório, Andréa Kedima Diniz Cavalcanti; Duque, Marcos André Araújo; Araújo, Mônica Modesto; Maia, Lenieé Campos; de Pontes Filho, Nicodemos Teles; de Melo-Júnior, Mário Ribeiro (Revista de Ciências Médicas e Biológicas, 2017)
Introduction: syphilis is a sexually transmitted disease caused by mycobacterium Treponema pallidum in which in its tertiary stage can lead to an aortic syphilitic aneurysm. Currently, such cases are rare because of the effectiveness of antibiotic therapy. Objective: we aimed to carry out an anatomopathological analysis and histopathological examination of three cases potentially suspicious of aortic syphilitic aneurysm on human corpses. Methods: It was a descriptive study which 03 anatomic specimens of aortas from cadavers with ages ranging from 50 to 91 years obtained in Service checklist of deaths during the period from 2014 to 2015. We performed an anatomopathological and histopathological analysis with the use of special dyes. Results: through the macroscopic evaluation it was observed in all cases a dilation corresponding to arch of aorta where the intima obtained an aspect of longitudinal striation, classic of syphilitic process. As for histopathological study on the tissues treatment with the staining batteries, it was demonstrated the presence of the dissecting hematoma in all cases, besides necrosis and absence characteristic of the inflammatory process. Conclusion: the anatomopathological and histopathological study are diagnostic tools which have specific characteristics and are directed to assist in preliminary diagnosis of suspected cases of aortic syphilitic aneurysm in necropsies.